How to Overcome Anemia in Adolescents Through Nutrition Education and Feeding Mung Bean Juice at Al Hadi Islamic Boarding School, Banten, Indonesia - Husnul Khotimah; Dadang Rochman; Trio Gustin Rahayu; Kety Soraya (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Adolescent girls require special attention in terms of iron requirements due to growth and the arrival of menstruation, so that adolescent girls are very susceptible to anemia. Prevention of anemia in teenagers can be done by providing education to teenagers about nutrition and increasing consumption of nutritious foods such as green bean juice drinks. This community service activity uses the Community Development (community empowerment) method. The activity was carried out in February 2024. The location of the activity is the Al Hadi Banten Islamic Boarding School with a target of 40 girl teenagers. This activity is a health examination, education about nutrition and giving mung bean juice. The post test scores showed changes in the form of increasing teenagers' knowledge about nutrition and increasing teenagers' Hemoglobin (Hb) levels after being given intervention in the form of mung bean juice. Providing education about adolescent nutrition and providing mung bean juice can effectively prevent anemia in adolescents.